Comparison of portal and ultrasound verification using PortalVision and SonArray during radiotherapy in prostate cancer patients - Bodusz, Dawid; Miszczyk, Leszek (Contemporary Oncology/Współczesna Onkologia, 2010)
Background : The main problems of contemporary radiotherapy in prostate cancer patients are prostate mobility and setup errors. Therefore, a new radiotherapy technique, image-guided radiotherapy (IGRT), was implemented. From the various available image-guided techniques, two – PortalVision and SonArray – were compared. PortalVision allows one to avoid setup errors but excludes prostate mobility. SonArray, based on ultrasound, enables visualization of soft tissues and precise target localization. Material and methods : Seventeen prostate cancer patients were treated in the Radiotherapy Department of the Centre of Oncology in Gliwice using conformal radiotherapy or IMRT technique. The prime method of patient positioning was ultrasound verification. During several treatment sessions, before ultrasound, portal images in AP and lateral projection were taken. Next, shifts calculated on the basis of PV were compared to shifts calculated with SonArray. Results : The means and standard deviations of shifts (cm) in EPID (portal verification) were: 0.12 with SD = 0.14 in anterior-posterior (AP) direction, 0.92 with SD = 0.83 in superior-inferior (SI) direction and 0.25 with SD = 0.24 in left-right (LR) direction. In ultrasound verification, the means and standard deviation of shifts in AP, SI and LR directions were: 0.37 cm with SD = 0.27 cm, 0.72 cm with SD = 0.80, and 0.25 cm with SD = 0.25 cm, respectively. A significant difference was found for anterior-posterior (p = 0.0000005) and superior-inferior (p = 0.0416461) direction. Conclusions : The shifts calculated on the basis of PV are different from those calculated with SonArray. Because the prostate is invisible in portal images, patient positioning based on ultrasound is probably a more reliable method which enables better correction of irradiated prostate cancer patients’ position.